2018
DOI: 10.1002/adma.201804541
|View full text |Cite
|
Sign up to set email alerts
|

Highly In‐Plane Anisotropic 2D GeAs2 for Polarization‐Sensitive Photodetection

Abstract: Due to the intriguing anisotropic optical and electrical properties, low‐symmetry 2D materials are attracting a lot of interest both for fundamental studies and fabricating novel electronic and optoelectronic devices. Identifying new promising low‐symmetry 2D materials will be rewarding toward the evolution of nanoelectronics and nano‐optoelectronics. In this work, germanium diarsenide (GeAs2), a group IV–V semiconductor with novel low‐symmetry puckered structure, is introduced as a favorable highly anisotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 59 publications
3
156
0
Order By: Relevance
“…Moreover, Guo et al reported a polarization‐sensitive medium wavelength infrared BP phototransistor, which can operate at wavelength of 3.39 μm and at low power in picowatts range . Figure F shows the typical schematic of the polarization‐sensitive photodetector of GeAs 2 , similar polarization‐sensitive photodetectors have also been fabricated on ReS 2 GeSe, ReSe 2 and ReS 2 Se 2(1‐ x ) . Recently, our group reported the polarization‐sensitive photodetector based on highly anisotropic 2D GeAs 2 with a dichroic ratio up to 2, and we found that polarization‐dependent photocurrent stem from GeAs 2 itself, since both the polarization‐dependent photoreponse and reflectance contrast display similar polarization‐dependent behavior .…”
Section: Applicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, Guo et al reported a polarization‐sensitive medium wavelength infrared BP phototransistor, which can operate at wavelength of 3.39 μm and at low power in picowatts range . Figure F shows the typical schematic of the polarization‐sensitive photodetector of GeAs 2 , similar polarization‐sensitive photodetectors have also been fabricated on ReS 2 GeSe, ReSe 2 and ReS 2 Se 2(1‐ x ) . Recently, our group reported the polarization‐sensitive photodetector based on highly anisotropic 2D GeAs 2 with a dichroic ratio up to 2, and we found that polarization‐dependent photocurrent stem from GeAs 2 itself, since both the polarization‐dependent photoreponse and reflectance contrast display similar polarization‐dependent behavior .…”
Section: Applicationsmentioning
confidence: 98%
“…Reproduced with permission from ref. Copyright 2018, Wiley‐VCH. G, Anisotropic photocurrent response of TaIrTe 4 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered tin phosphide, Sn 4 P 3 , has been studied for lithium‐ion and sodium‐ion battery applications and has been proven to be a promising material . Pnictides of lighter tetrels such as GeAs, SiAs, GeP, SiP, GeAs 2 , and SiAs 2 have been gaining interest in the field of thermoelectrics, photovoltaics, water splitting, and optics owing to their anisotropic nature, weak interlayer interactions, relatively small band gaps (<2 eV), and potential for tuning of properties through doping and strain …”
Section: Introductionmentioning
confidence: 99%
“…Binary alloys of group IV–V elements (AB, A═Si, Ge and B═P, As) adopting layered structures provide us another family of 2D materials. Based on the well‐known top‐to‐down synthesizing strategy, few‐layered group IV–V compounds have been experimentally realized . These 2D group IV–V compounds have attracted much scientific interests due to their highly anisotropic properties benefit from their low‐symmetry structures.…”
Section: Calculated Lattice Parameters Space Group Layer Thicknessmentioning
confidence: 99%